2012
DOI: 10.1080/02755947.2012.728173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Variables and Species Interactions on Sport Fish Communities in Small Missouri Impoundments

Abstract: Small impoundments (<400 ha) are numerous and provide close‐to‐home fishing opportunities for anglers but may not support optimal sport fisheries. Most of these fisheries are managed by harvest regulations, but watershed and impoundment characteristics, poor water quality, or detrimental species interactions can also influence the desirability of fisheries. We examined the relative importance of watershed characteristics, impoundment morphology, water quality, and species interactions in explaining differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Bluegill CPUE was positively associated with largemouth bass CPUE and total phosphorus concentration (negative correlation with lake PC1). Michaletz et al (2012) and Bevil and Weber (2018) also found a positive relationship between the relative abundances of bluegills and largemouth bass; likely because both species have successful recruitment under similar environmental conditions. Bluegill has been found to be more abundant in more-productive waters than in less-productive waters (Aday et al 2003a;Michaletz et al 2012).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Bluegill CPUE was positively associated with largemouth bass CPUE and total phosphorus concentration (negative correlation with lake PC1). Michaletz et al (2012) and Bevil and Weber (2018) also found a positive relationship between the relative abundances of bluegills and largemouth bass; likely because both species have successful recruitment under similar environmental conditions. Bluegill has been found to be more abundant in more-productive waters than in less-productive waters (Aday et al 2003a;Michaletz et al 2012).…”
Section: Discussionmentioning
confidence: 77%
“…Surprisingly, gizzard shad CPUE was not included in the top models explaining TL95 of bluegill and was not correlated (all p> 0.39) with any bluegill TL variable. Water body productivity as indexed by Secchi depth, chlorophyll or total phosphorus has been associated both positively (Tomcko and Pierce 2001;Schultz et al 2008;Hoxmeier et al 2009;Michaletz et al 2012) and negatively (Hoxmeier et al 2009) with bluegill growth and size structure. The TL and age of bluegills at sexual maturity was positively associated with clearer water (greater Secchi depths).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakes (and abbreviations) highlighted in bold are treatment lakes followed by their respective reference lakes. Morphometric and mean water quality data are from Knowlton and Jones (2007); Jones et al (2008b); Michaletz et al (2012); the Limnology Laboratory, University of Missouri (unpublished data); and the Missouri Department of Conservation (unpublished data). Macrophyte coverage shows the means from this study (T = trace).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the equation for White Crappies was Morphometric and water quality variables for the crappie study lakes in Missouri (BLC = Black Crappie; WHC = White Crappie). Morphometric and water quality data are fromKnowlton and Jones (2007);Jones et al (2008);Michaletz et al (2012b); the Limnology Laboratory, University of Missouri (unpublished data); and the Missouri Department of Conservation (unpublished data).…”
mentioning
confidence: 99%